ANALISIS BUDAYA ORGANISASI PADA PANTI REHABILITASI MENTAL PRIMAGUNA DI SERPONG TANGERANG SELATAN - Surti Wardani; Dini M Sunarya; Ana Febriana (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The research aims to analyze the organizational culture at the Primaguna Mental Rehabilitation Center in Serpong, South Tangerang. Through qualitative descriptive method, the research used 15 informants with in depth interview as a primary data collective. The result indicates all employee understand of the two organizational culture which are professional and teamwork. It provides a role to improve employee performance by carrying out a meaning-making and control mechanism to guides and shapes the attitudes and behaviour of employees to be more disciplined and skilled. In general, the emotional relationship of the employees already established well. The role of key executives is important in the process of directing and socializing for employees. To improve team orientation, superiors appoint people in the sub-teams for mutual coordination and cooperation in building a solid team. The inhibiting factors were found. The first is come from internal factor, the employees, low enthusiasm and initiative of the employees that affect the employee performance, the employee saturation caused by daily routines and no training programs were given to develop their skills. Second is the external factor of inadequate facilities and infrastructure, such as limited sport facilities, limited supply of PPE (Personal Protective Equipment), and incomplete the procurement of medical equipment.